Found [videorecording (DVD)] - Alford, David; Stam, Joseph; Stam, Joseph; Piper, Wendy; Henderson, Ryan; Bullen, Elijah (Bridgestone Multimedia Group, 2021)
A teenage boy raised entirely "off the grid" in the Appalachian Mountains, suddenly finds himself homeless, alone, and lost in a hi-tech modern world that he has never known before. A sympathetic deputy sheriff takes him out of the foster care system and into her home against the wishes of her troubled family. Problems grow from bad to worse as he discovers the truth about himself and uncovers secrets about his past that bring new meaning to the phrase "testing your faith."